2011
DOI: 10.1159/000329676
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Advances in Treating Periodontal Diseases

Abstract: Antibiotics are generally an efficient means of treating bacterial infections, and therefore are an obvious candidate in the treatment of periodontal diseases. Systemically and locally administered antimicrobial agents of all kinds have been evaluated in multiple clinical trials. The vast majority of studies have tested antibiotics as adjuncts to non-surgical debridement. No regime has demonstrated superiority over systemically administered amoxicillin and metronidazole in the treatment of any clinically or mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 93 publications
1
26
0
2
Order By: Relevance
“…Although these effects do not eradicate the subgingival biofilms as such, they may facilitate their disruption, by reducing the load of specific species. The most potent effect in the present in vitro experimental system is exerted by the combination of amoxicillin and metronidazole, a finding that supports the clinically proven treatment superiority of this regimen 11 . Whether prior detection of these species should guide the clinical decision for the selection of one, or any, of these antibiotic schemes cannot be deduced from this study, but there is merit for consideration in clinical investigations.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Although these effects do not eradicate the subgingival biofilms as such, they may facilitate their disruption, by reducing the load of specific species. The most potent effect in the present in vitro experimental system is exerted by the combination of amoxicillin and metronidazole, a finding that supports the clinically proven treatment superiority of this regimen 11 . Whether prior detection of these species should guide the clinical decision for the selection of one, or any, of these antibiotic schemes cannot be deduced from this study, but there is merit for consideration in clinical investigations.…”
Section: Discussionsupporting
confidence: 52%
“…Detection of high numbers of the red‐complex species ( Porphyromonas gingivalis , Tannerella forsythia , and Treponema denticola ) would be a suitable indication for the administration of metronidazole alone or (preferably) in combination with amoxicillin, a regimen that is also effective against Aggregatibacter actinomycetemcomitans and Gram‐positive pathogens 9,10 . Indeed, the systemic co‐administration of amoxicillin and metronidazole has demonstrated superiority over other antibiotic regimens in the treatment of clinically or microbiologically defined variants of periodontal disease 11,12 …”
mentioning
confidence: 99%
“…Antiseptic mouthwashes [18] and antibiotics is used to reduce the number of microorganisms [19]. In the case of administration of antibiotics, it is reported that antibiotics penetrated into the periapical lesions [20] and radicular cysts [21] in jaws.…”
Section: Discussionmentioning
confidence: 99%
“…Most evidence seems to exist for the beneficial effect of adjunctive systemic antibiotics and particularly for the combination of amoxicillin and metronidazole to non-surgical periodontal therapy [8,9,[69][70][71][72]. It has to be underlined that the systemic administration of antibiotics is only recommended in combination with mechanical debridement of the root surfaces i.e.…”
Section: Discussionmentioning
confidence: 99%